MAUSOLEUM OF SULTAN SADAT - Khaltursunov, Erkin; Khaitov , Narzullo (Eurasian Journal of Academic Research, 2022)
Sultan Saodat.complex is an architectural monument in Termiz (10th-17th centuries). This shrine, located in the east of Termiz, was formed in the 7th century. It includes about 20 mausoleums. There are mausoleums of the Sayyid dynasty.